mSphere of Influence: an Inupiat Journey in Science - Kathryn C. A. Milligan-McClellan (mSphere)
ABSTRACT Dr. Kathryn Milligan-McClellan works in the field of host-microbe interactions. In this mSphere of Influence article, she reflects on the people and scientific ideas that influenced her journey from a small town in Alaska to a faculty position at the University of Alaska Anchorage.